Relationships between plasma zinc and ferritin with nutritional status in thalassemic children - Luszy Arijanty; Sri Sudaryati Nasar; Bambang Madiyono; Djajadiman Gatot (Indonesian Pediatric Society Publishing House, 2016)
Background Repeated blood transfusions in thalassemic chil- dren can lead to iron overload in the body. High ferritin level leads to low plasma zinc status because of their competitive inhibition. Previous study found that there was a correlation between plasma zinc level and nutritional status. Objective To obtain plasma zinc level, to investigate the correla- tion between plasma zinc and ferritin, and the impact of plasma zinc on nutritional status in children with thallasemia. Methods A cross sectional study was conducted on 67 thalas- semic children. This study was performed at Thalassemia Center, Cipto Mangunkusumo Hospital, Jakarta, from 1 st until 31 st of March 2005. The age of the patients ranged from 4 to 18 years, with fer- ritin levels more than 2000 ng/ml during the last 6 months or total transfusion more than 5 liters. The subjects were divided into 2 groups, i.e. group 1 (4-10 years) and group 2 (>10-18 years). Di- etary intake was assessed by 3 day-dietary recall. The nutritional status were judged by mid upper arm circumference (MUAC) for age and height for age (H/A). Venous blood was obtained to mea- sure plasma zinc and ferritin levels. Statistical analysis was done by Student's t-test (2-tailed) and linear regression analysis. Results We found that 42% subjects were well-nourished, 51% were undernourished, and 7% were severely malnourished. All sub- jects had low plasma zinc status 31.9 (SD 16.9) μg/dl. There was a weak negative correlation between plasma zinc and ferritin level (r = -0.282, P=0.021). Lower zinc intake was detected in 65 out of 67 subjects. Conclusion All thalassemic children in our hospital had low plasma zinc level. There was a weak negative correlation between plasma zinc level and ferritin level. There was no significant correlation between plasma zinc status and nutritional status